Healthcare workforce well-being and its effect on patient care quality in the post-pandemic era - Pandey, Rashmi; Nirmal Chandu, Himanshu (Journal of Neonatal Surgery, 2025)
The well-being of healthcare workers plays a pivotal role in maintaining the quality of patient care, particularly in the post-pandemic era where healthcare systems are under heightened pressure. This study investigates the impact of healthcare workforce well-being on the quality of patient care, focusing on the challenges faced by healthcare professionals following the COVID-19 pandemic. The study examines various factors affecting the well-being of healthcare workers, including mental health, physical health, job satisfaction, work-life balance, and organizational support. A survey was conducted among healthcare workers, and data on their well-being and perceptions of patient care quality were analyzed. The findings reveal a significant correlation between healthcare workforce well-being and the perceived quality of patient care, with stressed, fatigued, or emotionally exhausted workers reporting lower levels of patient satisfaction and care quality. Moreover, institutional support, including mental health resources, adequate staffing, and work-life balance initiatives, was found to mitigate negative effects. The study emphasizes the importance of addressing healthcare worker well-being through systemic interventions to ensure high-quality patient care and improve healthcare outcomes in the post-pandemic era.